The alga Euglena gracilis stimulates Faecalibacterium in the gut and contributes to increased defecation - Ayaka Nakashima; Kengo Sasaki; Daisuke Sasaki; Kosuke Yasuda; Kengo Suzuki; Akihiko Kondo (Scientific Reports, 2021)
Abstract The alga Euglena gracilis (E. gracilis) has recently gained attention as a health food, but its effects on human gut microbiota remain unknown. This study aimed to determine the effect of E. gracilis on gut microbiota and defecation due to modulation of microbiota composition in vitro and in vivo. The in vitro model simulating human colonic microbiota revealed that E. gracilis addition stimulated the growth of commensal Faecalibacterium. Further, E. gracilis addition enhanced butyrate production by Faecalibacterium prausnitzii. Paramylon, an insoluble dietary fibre that accumulates in E. gracilis and is the main component of E. gracilis, did not stimulate Faecalibacterium growth in vitro. Daily ingestion of 2 g of E. gracilis for 30 days increased bowel movement frequency as well as stool volume in 28 human participants. Collectively, these findings indicate that E. gracilis components other than paramylon, stimulate the growth of Faecalibacterium to improve digestive health as well as promote defecation by increasing butyrate production.